Genotypic Diversity and Pre-Treatment Resistance Characteristic Analysis Among Newly Diagnosed HIV-1-Positive MSM from 2020-2022 in Jiaxing City, China - Zhang, Xiaofei; Ren, Ganglin; Ge, Zhijian; Lv, Shencong; Li, Ping; Song, Yin; Jia, Miaomiao; Zhou, Yamei; Yan, Yong; Zhu, Guoying (Current HIV Research, 2025)
BackgroundSince the first recorded HIV-1 infection in 1998, Jiaxing City has seen increasing HIV infections among men who have sex with men (MSM), necessitating targeted research to understand HIV-1 subtypes and drug resistance patterns to improve prevention and treatment strategies.ObjectivesThe study aimed to assess the variety of HIV-1 subtypes, the pre-treatment drug resistance (PDR) among MSM in Jiaxing, China, and transmission dynamics of drug-resistant strains. The findings may contribute to the development of targeted HIV prevention and control strategies for the MSM population.MethodsPlasma samples from all newly reported cases of HIV-1 transmitted through male-to-male sexual contact in Jiaxing City from 2020 to 2022 were retrospectively analyzed. Demographic and epidemiological data were collected. Partial pol gene regions were amplified, sequenced, and analyzed for drug resistance mutations (DRMs) using the Stanford HIV Drug Resistance Database. The Calibrated Population Resistance (CPR) program was utilised to identify Surveillance Drug Resistance Mutation (SDRM). A molecular transmission network was constructed to investigate the scale of transmitted drug resistance (TDR) strains.ResultsWe obtained a total of 298 eligible genetic sequences, revealing a diverse distribution of HIV-1 subtypes, with CRF07_BC, CRF01_AE, and CRF55_01B as the most prevalent. Pretreatment DRMs were detected in 91 cases (30.5%), yielding an overall PDR prevalence of 11.0%. Resistance to non-nucleoside reverse transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs) was most frequent (5.4% each). TDR prevalence reached 7.0%, showing an increasing trend (2020-2022). The molecular network analysis indicated sporadic dissemination of drug-resistant cases rather than large-scale transmission chains.ConclusionThe convergence of high HIV-1 subtype diversity, elevated PDR prevalence, rising TDR rates, and sporadic resistant strain transmission within MSM networks necessitates the sustained resistance surveillance and precision public health interventions.
Keywords: drug resistance